How Can We Reduce Dental Fear in Children? The Importance of the First Dental Visit - María Carrillo-Díaz; Blanca Carmen Migueláñez-Medrán; Carolina Nieto-Moraleda; Martín Romero-Maroto; María José González-Olmo (MDPI AG, 2021)
Dental fear is a common problem amongst children. It can affect children's psychological well-being, quality of life, and oral and systemic health. The aim of this study was to identify whether the patients' age at which visits to the paediatric dentist begin as well as the periodicity of these visits are factors that can prevent dental fear. This observational transversal study was conducted on 575 school children (average age 6.85 ± 0.78) and their mother/father/guardian. Parents completed a survey on the characteristics of dental visits and the child completed the index of dental anxiety and fear (IDAF-4C) to assess dental fear. The correlation between dental fear and age at first visit (r = −0.36 p < 0.01) and dental fear and frequency of visit (r = −0.65 p < 0.01) were statistically significant. The regression analysis performed showed that both variables predicted 44.4% of the dental fear in the child. In conclusion, the age of initiation to the paediatric dentist (before 2 years) and the periodic revisions (every 6 months or every year) could protect the child from dental fear.